Exploring the Impact of Human Resource Practices Mainly Training, Work Place Safety AMD Job Security on Career Growth in Uganda Christian University - Agape Mugabi (Uganda Christian University, 2024)
This study focused on exploring the impact of Human Resource practices mainly training, work place safety and job security on career growth. The study was carried out at Uganda Christian University. The objectives of the study were to: assess the perceived levels of job security among employees within UCU, evaluate the effectiveness of employee training programs in enhancing skill development and knowledge acquisition in UCU, examine the implementation of safety practices and their impact on employee well-being and work place safety perceptions and investigate the relationship between job security, employee training, and safety practices on employees’ perceptions of career growth opportunities in UCU. A population of 100 was used including the administrators and support staff members. A sample of 50 respondents was selected for the study purpose. The sample size was determined using Krejci and Morgan (1970). The data was collected using simple random sampling technique together with stratified random sampling technique which helped the researcher select the different categories of respondents. The findings revealed that the organisation has achieved its objectives through its effective human resource management that is in form of quality outputs, production on a large scale, efficient employees and a large number of committed workers. Followed by some of the respondents disagreeing that it has not yet achieved its objectives, from the findings. It indicated that this where the new employees of the organisation which have not spent there a large period of time. The study concluded that human resource plays a vital role in making an organisation to achieve its objectives hence UCU’s human resource management has a vital in its achievements. The study recommends that UCU should still carry on their ways of human resource practices since it has achieved a lot from it. The UCU should teach its employees on the importance of their activities such that employees work knowing that they are evaluated hence will increase more on their efficiency